Midcourse Guidance for Exoatmospheric Interception Using Response Surface Based Trajectory Shaping - Ann, Sungjun; Lee, Seokwon; Kim, Youdan; Ahn, Jaemyung (IEEE transactions on aerospace and electronic systems, 2020)
An exoatmospheric midcourse guidance law is proposed to intercept a ballistic missile during the free-flight phase. The proposed guidance law generates a thrust direction command for an antiballistic missile to hit the target at the predicted intercept point. For the predicted intercept point, the zero-effort-miss and zero-effort-velocity are determined based on the solutions of the two-body orbital boundary/initial value problems. The intercept point is predicted by using the trajectory shaping parameter that combines the zero effort trajectory and minimum time trajectory. A response surface model for the minimum interception time is constructed as a database, which is the polynomial function of the initial condition. The response surface model provides a predicted minimum time interception position for the midcourse guidance. Case studies are performed to demonstrate the performance of the proposed guidance law considering various uncertainties.